Otimização no uso de martelos e bigornas para quebrar sementes por macacos prego (Cebus flavius e C. libidinosus) no Bioma Caatinga - Emidio, Ricardo Almeida (2010)
Recently, capuchin monkeys (Cebus spp.) inhabitants of dry environments and with restriction of fleshy fruits, have been the subject of several studies regarding the use of instruments. During behaviour of using stones to crack open nuts there is evidence of selection of more effective hammers, as well as selection of anvils related to reducing the risk of predation. The aim of this study was to determine whether two groups of capuchin monkeys (C.flavius and and C.libidinosus) inhabitants of the Caatinga of Rio Grande do Norte make choice of hammers and anvils. The record of weight and location of stones indicated active choices of with what (choice of hammers) and where (selection of anvils) to crack open encapsulated seeds. The choice of hammers to break nuts depended on the type and degree of ripeness seed. Thus, smaller seeds were smashed with lighter hammers and larger seeds with heavier hammers. Still, C. flavius was the only species that presented a refinement in the choice of hammers that depended on the ripeness of seeds. For both species of capuchin monkeys studied, the nut-crack sites were not spread in accordance with the spatial distribution of seed-producing species, suggesting that the capuchin monkeys promote active choice of anvils. Thus, in environments with more escape routes through the trees, the nut-crack sites were found further apart than in regions that had less chance of escape through the trees. Also, there was a difference in the spacing of the anvils to depend on the type of seed: sites used to crack larger and more caloric seeds were found farther apart than the sites used to crack smaller and less caloric seeds, suggesting a pattern of avoiding direct competition. We conclude that the capuchin monkeys maximize energy savings and reduced risk of predation and the costs of food competition during the behaviour of using stones to crack open nuts